2021
DOI: 10.3390/pathogens10101340
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of HEV Infection and No Associated Risk of HEV Transmission from Mother to Child among Pregnant Women in Vietnam

Abstract: Infections with HEV in low- and middle-income countries (LMICs) are associated with increased rates of preterm birth, miscarriage, and stillbirth. The aim of the present study was to investigate HEV infections in pregnant women and the possibility of mother-to-child transmission, and associated outcomes. A total of 183 pregnant women in their third trimester were recruited and followed until delivery. Anti-HEV IgG and IgM were determined via enzyme-linked immunosorbent assay (ELISA), and HEV nucleic acids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(43 reference statements)
0
7
1
Order By: Relevance
“…Previous studies from Vietnam reported an anti-HEV IgG seroprevalence in the general population of 31% [7], which is comparable to the anti-HEV IgG seroprevalence observed in this study (26.8%). A very low anti-HEV IgM seroprevalence (0.5%) was observed in this study compared to other studies in Vietnam in occupationally unexposed individuals (6%) [7] and in pregnant women in the third trimester (2%) [4]. When comparing HEV seroprevalence in individuals who have frequent contact with pigs, such as pork vendors, pig farmers, and slaughterhouses workers, significantly high seropositivity for anti-HEV IgG (53%) and anti-HEV IgM (11.3%) was found in a study in Northern Vietnam [7].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Previous studies from Vietnam reported an anti-HEV IgG seroprevalence in the general population of 31% [7], which is comparable to the anti-HEV IgG seroprevalence observed in this study (26.8%). A very low anti-HEV IgM seroprevalence (0.5%) was observed in this study compared to other studies in Vietnam in occupationally unexposed individuals (6%) [7] and in pregnant women in the third trimester (2%) [4]. When comparing HEV seroprevalence in individuals who have frequent contact with pigs, such as pork vendors, pig farmers, and slaughterhouses workers, significantly high seropositivity for anti-HEV IgG (53%) and anti-HEV IgM (11.3%) was found in a study in Northern Vietnam [7].…”
Section: Discussioncontrasting
confidence: 78%
“…Viruses 2023, 15, 2075 2 of 8 HEV-4, and HEV-7) classified in the genus Paslahepevirus are known to infect humans [3]. HEV genotype 1 and genotype 2 (common in Asia and Africa) are mainly transmitted via the faecal-oral route and lead to acute hepatitis [2,4]. HEV genotype 3 and genotype 4 (in developed and developing countries) are transmitted mainly through the consumption of contaminated food, especially raw or undercooked pork.…”
Section: Introductionmentioning
confidence: 99%
“…2 Few cases of HEV genotype 3 infection during pregnancy were reported in immunocompetent patients. 3,4 No poor outcome was observed in this setting. Only 1 case of HEV genotype 3 infection that occurred during the first trimester in a kidney transplant patient was reported.…”
mentioning
confidence: 65%
“…In a study from Vietnam, no transmission to children from 4 immunocompetent pregnant women with HEV genotype 3a replication at delivery was observed. 4 To our knowledge, no delivery with replication HEV has been reported in solid organ transplant patients. Mallet et al 5 reported the case of a kidney transplant patient who was infected by HEV (unknown genotype) at 8 wk of gestation.…”
Section: Discussionmentioning
confidence: 93%
“…The applicable volume of rectal swabs and the feces suspension was centrifuged at 10,000×g for 2 minutes to remove solids from the sample, while 0.1 mg liver tissues were homogenized with a sterilized mortar and pestle with 1,000 µL PBS. Then, using the QIAamp Viral RNA Mini Kit (Qiagen; Catalog #52906, Lot #166024216, Hilden, Germany), process 140 μL of supernatant from 3 kinds of samples according to the manufacturer's instructions [21]. Complementary DNA (cDNA) synthesis was performed using the RevertAid First Strand cDNA Synthesis Kit (Thermo Scientific, Waltham, MA, USA).…”
Section: Sample Collectionmentioning
confidence: 99%